The Impact of the Age of Independent Eating Initiation on Preschool Children's Fine Motor Development: A Case-Control Study - Wati, Putu Erna Sintya; Thanaya, Sayu Aryantari Putri; Antari, Ni Komang Ayu Juni; Adhitya, I Putu Gde Surya (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi Indonesia, 2025)
Background : Independent eating requires optimal fine motor development, including hand coordination, chewing, and swallowing. However, research on how the age of independent eating initiation affects fine motor development remains limited. This study aims to investigate the relationship between the age of independent eating initiation and fine motor development in preschool children. Methods : The sample consisted of 135 preschool children (45 cases and 90 controls) from five kindergartens in Pemecutan. Cases were defined as children with fine motor impairments based on the Denver II test, while controls were children with normal fine motor development. Information on the age at which children started eating independently was obtained through a parent-administered questionnaire. Data were analyzed using binary logistic regression to control for confounding variables. Results : Both univariate and multivariate analyses indicated a significant association between the age of independent eating initiation and fine motor development. After adjusting for confounding variables, compared to children who started eating independently at 0–12 months, the likelihood of fine motor impairment increased significantly with a later age of independent eating initiation: adjusted odds ratio (AOR) = 3.51 (p = 0.038) at 13–24 months, AOR = 13.77 (p = 0.000) at 25–36 months, and AOR = 17.35 (p = 0.000) at >36 months. Conclusion : The findings indicate a significant relationship between the age of independent eating initiation and fine motor development in preschool children. A delay in independent eating initiation is associated with an increased likelihood of fine motor impairment. However, this study has limitations, including potential parental recall bias and the inability of the case-control design to establish a causal relationship. Keywords : preschool children, independent eating, fine motor skills, age of independent eating initiation